Schizophrenia and the eye - Silverstein, Steven M. (Schizophr Res Cogn, 2015)
Although visual processing impairments are common in schizophrenia, it is not clear to what extent these originate in the eye vs. the brain. This review highlights potential contributions, from the retina and other structures of the eye, to visual processing impairments in schizophrenia and high-risk states. A second goal is to evaluate the status of retinal abnormalities as biomarkers for schizophrenia. The review was motivated by known retinal changes in other disorders (e.g., Parkinson’s disease, multiple sclerosis), and their relationships to perceptual and cognitive impairments, and disease progression therein. The evidence reviewed suggests two major conclusions. One is that there are multiple structural and functional disturbances of the eye in schizophrenia, all of which could be factors in the visual disturbances of patients. These include retinal venule widening, retinal nerve fiber layer thinning, dopaminergic abnormalities, abnormal ouput of retinal cells as measured by electroretinography (ERG), maculopathies and retinopathies, cataracts, poor acuity, and strabismus. Some of these are likely to be illness-related, whereas others may be due to medication or comorbid conditions. The second conclusion is that certain retinal findings can serve as biomarkers of neural pathology, and disease progression, in schizophrenia. The strongest evidence for this to date involves findings of widened retinal venules, thinning of the retinal nerve fiber layer, and abnormal ERG amplitudes. These data suggest that a greater understanding of the contribution of retinal and other ocular pathology to the visual and cognitive disturbances of schizophrenia is warranted, and that retinal changes have untapped clinical utility.